2003
DOI: 10.1021/la034348u
|View full text |Cite
|
Sign up to set email alerts
|

Nonspecific and Thiol-Specific Binding of DNA to Gold Nanoparticles

Abstract: Modifying colloidal gold particles with DNA is a new interesting approach in the development of genetic biosensors. Normally the modification is designed to consist of a covalent gold−sulfur bond mediated by a thiol group on one end of a single-stranded oligonucleotide. Here we investigate to what extent the binding actually consists of only the sulfur bridge or if some other nonspecific binding mechanism is present as well. We report on an electrophoresis study showing high amounts of strong, non-thiol-mediat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
149
0
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 161 publications
(160 citation statements)
references
References 21 publications
9
149
0
2
Order By: Relevance
“…22,23 The generally accepted adsorption model for this process is shown in Figure 1B, where DNA wraps around the AuNP. 22,[24][25][26] The adsorption of non-thiolated DNA has also found important applications in analytical chemistry, [27][28][29][30][31][32][33][34] polymerase chain reactions, 35,36 nanoparticle synthesis, 37,38 and medicine. 37,39 We recently reported that at neutral pH, each 13 nm AuNP adsorbs just around twenty 12-mer DNAs even after overnight incubation, 40 which is consistent with the results from the literature using polyadenosine (e.g A20) as an anchoring block for DNA adsorption with the salt aging approach.…”
Section: This Document Is the Accepted Manuscript Version Of A Publismentioning
confidence: 99%
“…22,23 The generally accepted adsorption model for this process is shown in Figure 1B, where DNA wraps around the AuNP. 22,[24][25][26] The adsorption of non-thiolated DNA has also found important applications in analytical chemistry, [27][28][29][30][31][32][33][34] polymerase chain reactions, 35,36 nanoparticle synthesis, 37,38 and medicine. 37,39 We recently reported that at neutral pH, each 13 nm AuNP adsorbs just around twenty 12-mer DNAs even after overnight incubation, 40 which is consistent with the results from the literature using polyadenosine (e.g A20) as an anchoring block for DNA adsorption with the salt aging approach.…”
Section: This Document Is the Accepted Manuscript Version Of A Publismentioning
confidence: 99%
“…The prediction was also confirmed by comparing the results of gel electrophoresis. Furthermore, gel electrophoresis has been previously utilised in nanotechnology to investigate the biding behaviour of L-lysine [24], to separate DNA-capped nanogold [25,26] and protein-capped GNPs [27].…”
Section: Introductionmentioning
confidence: 99%
“…Following the same theme, the coating of citrate-stabilized AuNPs with bovine serum albumin (BSA) through electrostatic interactions has been demonstrated [38]. Non-specific binding has also been shown between single strand DNA and the surface of colloidal gold particles [31,32].…”
Section: Introductionmentioning
confidence: 91%
“…'Grafting-to' [22,[29][30][31][32][33][34][35][36][37][38] is now the accepted nomenclature for post modification of the surface of a colloidal dispersion using pre-synthesized polymers. Boyer et al [29] showed how a chemical affinity could result in the directed adsorption of functional end groups (thiol and trithiocarbonate) of block copolymers constructed from PEG analogues onto the surface of citrate-stabilized gold nanoparticles (AuNPs).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation